La equinoterapia y el desarrollo humano. - Bonilla Camacho, Ana María (2018)
Equestrian therapies on balance development, pathologies and social interaction in patients with biological or behavioral affectations are the research center for assessment and diagnosis of the effect that causes corporal temperature and rhythmic impulses of the equine, this in front of the influence on the individual at social interaction are the central axis of the research project THE EQUINOTHERAPY AND HUMAN DEVELOPMENT at Bellavista Center located on Saquisilí Canton, Cotopaxi Province. The methodology used was descriptive one since the direct link with the center of equinotherapy was experienced on activities that are carried out as part of the stimulation that develops in infants with cognitive, psychomotor or affective problems; from this is concluded that the protocol that they use at therapies of development, factors that affect the stimulation process that is carried out with children are detected, such as: the body temperature of the animal that influences on health conditions of the animal. patient, the pattern of locomotion is displayed to start equine therapy as an important step at this therapy. On the other hand, this center has the largest attendance of people with Down syndrome as the main condition that presents, hyperactivity, autism and behavioral problems, followed by difficulties of attention and mental concentration, regardless of sex and age are the most frequent, so the work deployed has a broad coverage to justify the importance of this job.